Comparative Study of the Performance of Three Modeling Approaches for a Photovoltaic Panel Emulator based on the Single-diode Model and Using a Buck-boost DC/DC Converter - S. , Jenkal; M. , Kourchi; A. , Rachdy; O. , Oussalem; Idadoub, H.; M. , Oubella; M. , Ajaamoum (International Journal of Psychosocial Rehabilitation, 2020)
The photovoltaic emulator provides an efficient solution to maintain the same current-voltage output of the photovoltaic module. It includes three major parts: the photovoltaic model, a controlling strategy, and a converter for the power stage. The precise determination of the current-voltage characteristic curve is a challenge for the researchers to this day. This paper provides three approaches for the modeling of photovoltaic arrays and presents the synthesis results by the simulation of the current-voltage characteristic performances obtained by the modeling approaches. Then an evaluation of the photovoltaic emulator’s behavior under different conditions. An identification method is developed using Newton Raphson’s and linear interpolation methods. The mathematical model is built using MATLAB/SIMULINK and a sized buck-boost converter for the power stage. Following this comparative study, we came to a high agreement between the experimental and simulated current-voltage characteristics for the emulator under study.